Pengaruh Literasi Digital, Atmosfer Akademik, Dan Pengalaman Magang Terhadap Kesiapan Kerja Mahasiswa S1 Manajemen Di Universitas Dharma Andalas - Gusnita, Gusnita; Mellyna Eka Yan Fitri (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to determine the influence of Digital Literacy, Academic Atmosphere, and Internship Experience on the Work Readiness of students in the Faculty of Economics and Business at Dharma Andalas University. The population in this study consists of active undergraduate Management students from the 2018 to 2024 cohorts, totaling 517 students. The sample for this study consists of 114 students, specifically active students from the 2020 and 2021 cohorts, as they are considered proficient in using digital devices due to the implementation of online learning during COVID-19, and students who have taken internship courses. This study is categorized as quantitative research. The instrument used in this research is a questionnaire. The results of the study, using multiple linear regression analysis, indicate that digital literacy, academic atmosphere, and internship experience simultaneously have a significant influence on work readiness. Additionally, digital literacy has a positive partial effect on work readiness, the academic atmosphere has a positive partial effect on work readiness, and internship experience has a positive partial effect on work readiness.